DOES THE PRESENCE OF WOMEN ON THE AUDIT COMMITTEE AFFECT AUDIT FEES? EMPIRICAL EVIDENCE FROM THE BANKING INDUSTRY IN INDONESIA - Silvi Nur Aisyah; Samsul Rosadi (P3I UMSurabaya, 2024)
The aim of this research is to investigate the relationship between female representation on audit committees and audit fees, considering various factors. The research methodology employed is multiple linear regression analysis. Data was gathered from secondary sources, specifically the banking industry listed on the IDX between 2018 and 2022, utilizing specific criteria. The analysis encompassed the presence and proportion of female audit committee chairs, employing purposive sampling. This research endeavors to shed light on whether female audit committee chairs exert a significant positive influence on audit fees. It aims to offer a clearer perspective on the impact of female representation at the leadership level of audit committees on audit fees. The findings reveal that female audit committee chairs significantly affect audit fees positively, while the proportion of female audit committee chairs has a significant negative impact on audit fees. Consequently, the banking industry in Indonesia could contemplate appointing female audit committee chairs to mitigate their company's risks.